2003
DOI: 10.1208/pt040458
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol generation by metered-dose inhalers containing dimethyl ether/propane inverse microemulsions

Abstract: Water soluble compounds were incorporated into metered-dose inhalers (MDIs) by using water-in-propellant lecithin microemulsions, in which dimethyl ether (DME) and propane acted as both continuous phase and propellant. Lecithin, water, and water soluble compounds were added to glass MDI containers, valves were crimped on, and propellants were added using a pressure burette. Aerosols were produced using commercially available actuators, and inertial impaction was used to determine the mass median aerodynamic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Additionally, the half-life of these HFA propellants in the atmosphere is a fraction of that of the CFCs they replaced (3). Other propellants have been explored as replacements for CFCs, namely, 1,1-difluoroethane (HFA 152a), propane, n-butane, isobutane, n-pentane, isopentane, neopentane, dimethylether, and hydrofluoro-olefins (HFO) (18)(19)(20)(21)(22)(23)(24). Many of these propellants have not been extensively studied and toxicological risks have not been assessed because they are flammable and thus pose an inherent safety risk.…”
Section: The Transition From Cfcs To Hfasmentioning
confidence: 99%
“…Additionally, the half-life of these HFA propellants in the atmosphere is a fraction of that of the CFCs they replaced (3). Other propellants have been explored as replacements for CFCs, namely, 1,1-difluoroethane (HFA 152a), propane, n-butane, isobutane, n-pentane, isopentane, neopentane, dimethylether, and hydrofluoro-olefins (HFO) (18)(19)(20)(21)(22)(23)(24). Many of these propellants have not been extensively studied and toxicological risks have not been assessed because they are flammable and thus pose an inherent safety risk.…”
Section: The Transition From Cfcs To Hfasmentioning
confidence: 99%
“…Particle size and potential toxicity of excipients are critical factors that limit the use of microparticles for pulmonary administration. The deepest penetration of particles into airways and their deposition in peripheral regions are achieved when the particle size ranges between 1 and 5 µm (7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Excipients must be physiologically acceptable, biodegradable, and nonimmunogenic and might not induce inflammatory and alloreactive responses (18).…”
Section: Introductionmentioning
confidence: 99%
“…Although authors have suggested using nanoemulsion formulations for inflammation [2][3][4][5][6][7]. Budesonide (16,17-butylidenebis(oxy)-11,21-dihydroxypregna-1,4diene-3,20-dione) is a synthetic glucocorticoid steroid used in the treatment of asthma and an inflammatory bowel disease [9]. Molecular weight of budesonide is 430.5, log p values are 3.2, biopharmaceutical classification system Class II and practically insoluble in water (28 µg/mL) [10].…”
Section: Research Articlementioning
confidence: 99%